2008
DOI: 10.1530/eje-07-0357
|View full text |Cite
|
Sign up to set email alerts
|

Changes in heart rate variability and QT dispersion in patients with overt hypothyroidism

Abstract: Objective: The aim of the present study was to evaluate the effect of clinical hypothyroidism on cardiovascular autonomic function and ventricular repolarization. Design and methods: We studied 31 patients (22 females and 9 males; mean age 53.6G11.8 years) with overt hypothyroidism (TSHZ56.2G14.7 mU/ml, low free thyroxine (T 4 ), free tri-iodothyronine (T 3 )) and 31 euthyroid controls, to investigate the dispersion of the QT interval in electrocardiogram (ECG) (an index of inhomogeneity of repolarization) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
89
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 28 publications
8
89
0
Order By: Relevance
“…High plasma norepinephrine levels have been seen in hypothyroidism, but the responsiveness to endogenous catecholamine is decreased, because of a decrease in the number of beta adrenergic receptors and their desensitization to the effect of catecholamine. This autonomic dysfunction can be partly restored after replacement treatment with levothyroxine [7]. …”
Section: Discussionmentioning
confidence: 99%
“…High plasma norepinephrine levels have been seen in hypothyroidism, but the responsiveness to endogenous catecholamine is decreased, because of a decrease in the number of beta adrenergic receptors and their desensitization to the effect of catecholamine. This autonomic dysfunction can be partly restored after replacement treatment with levothyroxine [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Canpolat et al (2011) have also shown disturbed HRV parameters in familial Mediterranean fever, another autoinflammatory disorder. Although altered cardiac autonomic balance has been shown in the hypothyroid and subclinically hypothyroid patients with Hashimoto thyroiditis, there is not any study on the evaluation of cardiac autonomic functions in euthyroid children with Hashimoto thyroiditis (Galetta et al 2008). VLDL-cholesterol (mg/dL) 17.7 ± 6.5 15.4 ± 7.4…”
Section: Discussionmentioning
confidence: 99%
“…According to some researchers, the HRV alterations in hypothyroidism and subclinical hypothyroidism can be reversed by levothyroxine therapy (Galetta et al 2006(Galetta et al , 2008. Padberg et al (2001) have reported reduction in anti-TPO antibodies and B lymphocyte counts in adults with eHT in response to levothyroxine prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hypothyroid patients are more prone to ventricular arrhythmias, due to increased electrical dispersion in the myocardium [7].…”
Section: Discussionmentioning
confidence: 99%